TEACHING STATISTIC USING MATLAB - Yuliani, Oni (KURVATEK, 2019)
This paper is to describe the use of Matlab as a scientific tool for the teaching of statistics in undergraduateschool. Application of this software in the teaching of some difficult topics like probability concepts, probabilitydistribution, statistical significance, and significance tests, were demonstrated using the Matlab. Matlab has proved it self to be a very effective tool in the educational process because it offers a simple and powerful tool for analyzing and visualizing results of numerical simulations and measurements.